The Effectiveness of the Think Talk Write Learning Model Assisted by Animated Video on Elementary School Students’ Mathematics Learning Outcomes - Mila Wati; Firdaus; Sitti Rahmi (Journal of Primary Education Innovation and Research, 2025)
This study aimed to determine the effectiveness of the think-talk-write learning model assisted by an animated video on the mathematics learning outcomes of fifth-grade students at SD Inpres 12/79 Lakukang, Kecamatan Mare, Kabupaten Bone. This study used a quantitative approach with a preexperimental research design. The research design applied was a one-group pretest–posttest design. The population of this study consisted of all fifthgrade students at SD Inpres 12/79 Lakukang, with a total sample of 20 students selected using saturated sampling. Data were collected through a multiple-choice test, student response questionnaire, and learning implementation observation sheet. The test was administered before and after the treatment to measure students’ mathematics learning outcomes. The data were analyzed using descriptive and inferential statistical analyses with the assistance of IBM SPSS Statistics for Windows, version 22.0. The results showed that the mean pretest score was 48.50, while the mean posttest score increased to 83.00. The student response questionnaire obtained an average percentage of 87.70%, which was categorized as very good. The implementation of the learning process obtained an average score of 96.66%, which was categorized as very well implemented. The results of the pairedsample t-test showed that the t-count value was 7.212, which was higher than the t-table value of 2.093. Therefore, the null hypothesis was rejected, and the alternative hypothesis was accepted. These findings indicate that the Think Talk Write learning model assisted by animated video is effective in improving the mathematics learning outcomes of fifth-grade students.